Ulcerative colitis: An uncommon cause of hematochezia in children of preschool age group (Indian Journal of Case Reports, 2020)
Inflammatory bowel disease (IBD) is a perplexing disease characterized by chronic mucosal inflammation. It results from a complex interplay of various factors including genetic and environmental and adaptive immunity of the host. Crohn’s disease and ulcerative colitis (UC) are the two broad phenotypes of IBD. The incidence of pediatric IBD seems to be increasing globally. The common age of presentation of pediatric IBD is between 5 and 15 years of age with a mean duration between the onset of symptoms and diagnosis being 96 months. Children usually present with the classic symptoms of weight loss, abdominal pain, and bloody diarrhea. They may sometimes present with non-classic symptoms of poor growth, anemia, or extraintestinal manifestations. We report a case of UC in a 5-year-old child in whom the diagnosis was clinched within 1 month of onset of symptoms.